Quantifying the influence of sub-mesoscale dynamics on the supply of iron to Southern Ocean phytoplankton blooms. (September 2016) - Rosso, Isabella; Hogg, Andrew McC.; Matear, Richard; Strutton, Peter G.
Abstract: Southern Ocean phytoplankton growth is limited by iron. Episodes of natural iron fertilisation are pivotal to triggering phytoplankton blooms in this region, the Kerguelen Plateau bloom being one prominent example. Numerous physical mechanisms that may supply iron to the euphotic zone in the Kerguelen Plateau region, and hence trigger a phytoplankton bloom, have been identified. However, the impact of sub-mesoscale flows in delivering iron has been omitted. With a scale of order 10 km, sub-mesoscale filaments and fronts can dramatically increase vertical velocities and iron transport. An innovative technique is developed to investigate the role of vertical advection associated with sub-mesoscale features on the supply of iron to the photic zone. First, Lagrangian trajectories are calculated using three dimensional velocity fields from high resolution numerical simulations; iron concentration is then computed along these Lagrangian trajectories. The contribution of mesoscale- (1/20° resolution) and sub-mesoscale-resolving models (1/80° resolution) is compared, thereby revealing the sensitivity of iron supply to horizontal resolution. Iron fluxes are clearly enhanced by a factor of 2 with the resolution, thus showing that the vertical motion induced by the sub-mesoscales represents a previously neglected process to drive iron into the photic waters of the Kerguelen Plateau. Abstract : Highlights: We investigate iron supply due to sub-mesoscale dynamics in the Kerguelen Plateau region. We develop a new technique to evaluate iron concentration, built on Lagrangian experiments. We contrast results from mesoscale- and sub-mesoscale-resolving models. The sensitivity on the resolution of iron fluxes depends on the location. Iron fluxes can be enhanced by up to a factor of two due to submesoscale processes.